Pembelajaran Matematika Berbasis Konteks Kehidupan Sehari-Hari untuk Meningkatkan Literasi Matematika Siswa: Kajian Literatur - Nurul Azizah Ritonga; Mariatul Kiftia Shakila; Nidia Lestari (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to analyze various research results related to the application of context-based mathematics learning in improving students' mathematical literacy. Mathematical literacy is an important skill that enables students to understand, use, and apply mathematical concepts and reasoning in solving various problems related to real life. This study uses a qualitative approach with a literature review method. Research data was obtained through a review of various scientific articles relevant to the research topic. The analysis process was carried out in several stages, namely identification of literature sources, selection of articles based on topic suitability, and synthesis of published research findings. The results of the study show that integrating everyday contexts into mathematics learning can improve students' conceptual understanding, mathematical reasoning abilities, and problem-solving skills. Learning that links mathematical material to real-life situations can also help students understand concepts more meaningfully and encourage active engagement in the learning process. The findings of this study provide an overview that the application of mathematics learning based on everyday life contexts can be an effective strategy in improving students' mathematical literacy. Therefore, teachers need to design learning that links mathematical concepts to real-life situations so that students' mathematical literacy skills can develop optimally.